Electrocardiogram testing during athletic preparticipation physical examinations - O'Connor, D. P.; Knoblauch, M. A. (Journal of Athletic Training, 2010)
Context: Sudden cardiac death (SCD) is a relatively rare yet unfortunate risk of athletic participation. To reduce the incidence of SCD, electrocardiogram (ECG) use during athletic preparticipation examinations (PPEs) has been proposed to detect underlying cardiac abnormalities.